Waist-To-Height Ratio Is a More Accurate Tool for Predicting Hypertension Than Waist-To-Hip Circumference and BMI in Patients With Type 2 Diabetes: A Prospective Study - Moosaie, Fatemeh; Fatemi Abhari, Seyede Marzie; Deravi, Niloofar; Karimi Behnagh, Arman; Esteghamati, Sadaf; Dehghani Firouzabadi, Fatemeh; Rabizadeh, Soghra; Nakhjavani, Manouchehr; Esteghamati, Alireza (Frontiers in Public Health, 2021)
Background: Anthropometric measures [i.e., body mass index (BMI), waist-to-hip ratio (WHR), and waist-to-height ratio (WHtR)] have been used as prediction factors for incident hypertension. However, whether any of these measures is superior to another in the matter of accuracy in predicting hypertension in diabetic patients has been controversial. The present prospective study aimed to determine whether WHtR is a more accurate tool for predicting hypertension than WHR and BMI in patients with type 2 diabetes. Methods: The study population consisted of 1,685 normotensive patients with type 2 diabetes. BMI, WHR, and WHtR were assessed at baseline and followed up for hypertension incidence for a mean of 4.8 years. A cox regression analysis was performed to assess the association between anthropometric measures (i.e., BMI, WHR, and WHtR) and incident hypertension during the follow-up period. The area under the ROC curve analysis was performed and optimal cutoff values were calculated for each anthropometric measure for hypertension prediction. Results: WHtR and BMI were significantly associated with an increased incidence of hypertension (HR = 3.296 (0.936–12.857), P < 0.001, and HR = 1.050 (1.030–1.070), P < 0.001, respectively). The discriminative powers for each anthropometric index for hypertension were 0.571 (0.540–0.602) for BMI, 0.518 (0.486–0.550) for WHR, and 0.609 (0.578–0.639) for WHtR. The optimal cutoff points for predicting hypertension in patients with type 2 diabetes were 26.94 (sensitivity = 0.739, specificity = 0.380) for BMI, 0.90 (sensitivity = 0.718, specificity = 0.279) for WHR, and 0.59 (sensitivity = 0.676, specificity = 0.517) for WHtR. Conclusion: WHtR was a more accurate tool for predicting hypertension compared to WHR and BMI in patients with type 2 diabetes.